Gray area between policy success and failure: Assessing the degree of success of Law Number 7 of 2016 in the salt industrialization program in West Nusa Tenggara Province - Antun Mardiyanta; Donny Ermawan (Masyarakat, Kebudayaan dan Politik, 2023)
Salt problems in Indonesia are quite complex and persistent, including reliance on imports, low quality, poor trade administration, and high costs. The central government has issued a policy that protects salt farmers, regulates salt imports, and implements the PUGaR program. The NTB Provincial Government as the fourth largest contributor to salt production in Indonesia has a Salt Industrialization Program policy. This article analyzed the existing policies for overcoming the problems and achieving the expected results. Using a descriptive qualitative research method with Policy Success theory proposed by Allan McConnell as its analytical tool, this article examines the success/failure of salt policy from the process, program, and political dimensions, as well as the level of success using the degree of policy success/failure. The results of the study showed that the criterion for maintaining policy objectives/instruments and policy legitimacy on the process dimension is included in tolerable failure because there is still a failure to maintain objectives and legitimacy even though it is not significant. The criterion for building a sustainable coalition is included in conflicted failures because it has not involved all stakeholders in policy formulation. In the program dimension, the criteria for implementation that is aligned with objectives, achieving the expected outcomes, and providing benefits for the target group are included in the conflicted failure category because there are balanced conditions between success and failure. Meanwhile, the political dimension cannot be measured because it still receives minimal public attention.